Deep seismic reflection profiling over the Siwalik fold belt of NW Himalaya - Prasad, B Rajendra; Rao, V Vijaya; Tewari, HC (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1301 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.111-112